Collective homeostasis of condensation-prone proteins via their mRNAs - Rupert Faraway; Neve Costello Heaven; Holly Digby; Klara Kuret Hodnik; Jure Rebselj; Oscar G. Wilkins; Anob M. Chakrabarti; Ira A. Iosub; Neža Vadnjal; Rhys Dore; Lea Knez; Stefan L. Ameres; et al. (Nature, 2025)
Abstract The concentration of proteins containing intrinsically disordered regions must be tightly controlled to maintain cellular homeostasis 1,2 . However, mechanisms for collective control of these proteins, which tend to localize to membraneless condensates, are less understood than pathways mediated by membrane-bound organelles 3,4 . Here we report ‘interstasis’, a homeostatic mechanism in which increased concentration of proteins within RNA–protein condensates induces the sequestration of their own mRNAs. The selectivity of interstatic mRNA capture relies on the structure of the genetic code and conserved codon biases, which ensure that similar multivalent RNA regions encode similar low-complexity domains. For example, arginine-enriched mixed charge domains (R-MCDs) tend to be encoded by repetitive purine-rich sequences in mRNAs. Accumulation of proteins containing R-MCDs increases the cohesion of nuclear speckles, which induces selective capture of purine-rich multivalent mRNAs. The multivalent regions are bound by specific RNA-binding proteins, including TRA2 proteins, which relocalize to speckles upon interstasis to promote selective mRNA capture. CLK-mediated phosphorylation of TRA2 proteins counters their localization to speckles, thereby modulating interstasis. Thus, the condensation properties of nuclear speckles act as a sensor for interstasis, a collective negative-feedback loop that co-regulates mRNAs of highly dosage-sensitive genes, which primarily encode nuclear condensation-prone proteins.